Potential effects of excessive Energy drinks consumption in young people on long-term cardiovascular risks - Kumar, Akhil; Jacson, Janice (Indian Journal of Pharmacy & Drug Studies, 2023)
Energy drinks have been recently associated with adverse outcomes. One of the prominent issues being considered is the link between the risk of developing cardiovascular diseases and energy drink consumption. The increasing concentration of caffeine accompanied by sugars, taurine, etc. are mainly responsible for these risks. In the long term, the children and the youth are vulnerable to the dangers of energy drink consumption. Attention needs to be given to the adverse cardiovascular effects in this population. Regulatory actions and future restrictions on the sale and consumption of these drinks can bring about positive attitudes in the minds of people and influence their patterns of energy drink consumption. This review gives a comprehensive picture of the various aspects related to energy drinks consumption, cardiovascular risks, risk in the younger population and regulatory actions to be implemented.